The Iranian elites as perceived from their society and the main geopolitical actors (Journal of the Spanish Institute for Strategic Studies, 2018)
This article proposes a non-conventional approach to the issue ofpolitical elites and the internal structures of power in Iran. Based onsome influential authors from critical theory, the text explains the ideasbehind the Islamic Revolution, the nature of the state and the rationalenurturing the ruling class. After a brief inquire into the current economiccontext of this oil-rich republic, we will sketch the main features of thisPersian-Azeri society which struggles between political agency and anacute alienation from the religious authorities. Finally, we will attempta «who’s who?» In the geopolitical relations of the IRI with a specialfocus on how the ongoing conflicts in the Middle East are shaping theelites and perhaps even shifting the global centers of power.
Keywords: Critical theory; Iranian society; Islamic Revolution; political elites; reformist faction; Shiite authorities